Environmental trade-offs of meeting nutritional requirements with a lower share of animal protein for adult subpopulations - J. Aubin; F. Vieux; S. Le Féon; M. Tharrey; J.L. Peyraud; N. Darmon (Animal)
Decreasing the share of protein contributed by animal-based foods is recommended to move towards more sustainable and healthier diets. This study aimed to assess the potential environmental impacts of diets with a lower share of animal protein. The diets were modeled to include the minimum share of animal protein in total protein that met nutrient requirements and did not increase costs. The new diets also minimized the difference in the quantity of food from those of observed (OBS) diets. They were modeled for five adult subpopulations (defined by sex and age) using mathematical optimization. The model was created by combining the INCA2 database (to model OBS diets in the French population) and a database of 207 food items to adjust nutritional and price parameters. All modeled diets satisfied nutritional and cost constraints. A low-animal-protein (LAP) diet was identified for each subpopulation by progressively decreasing the share of animal protein by steps of 5% until the recommended quantity of protein and/or consumption constraints were no longer satisfied. Potential environmental impacts of the LAP diets in eight impact categories were calculated using life cycle assessment and life cycle inventories from Agribalyse® 3.0. A LAP diet for the entire population was calculated as a weighted mean of the subpopulations’ LAP diets. The share of animal protein decreased from 70% in the OBS diet to 50% in the LAP diet. Compared to the OBS diet, the LAP diet decreased five environmental impacts: climate change (greenhouse gas emissions), acidification (emissions of acidifying compounds) and land occupation (all by more than 30%), cumulative energy demand (by 23%) and marine eutrophication (by 13%). Conversely, it increased three environmental impacts: freshwater eutrophication and water use (both by ca. 40%) and biodiversity damage potential (potential loss of species associated with land use) (by 66%). These results suggest that decreasing the share of animal protein to 50% is compatible with nutritional requirements, affordability and consumption constraints, but would have mixed effects on the environment.